Apple Tree Rootstocks [Malus sylvestris (L.) mill. Domestic var (Borkh) Mansf.] Under Water Stress - Rascón-Castillo, Mariela; Lozano-Martínez, Carlos Alberto; Jacobo-Cuellar, Juan Luis; Frias-Moreno, Maria Noemi; Cruz-Álvarez, Oscar; Hernández-Rodríguez, Ofélia Adriana; Ojeda-Barrios, Damaris Leopoldina; Parra-Quezada, Rafael Ángel (REVISTA TERRA LATINOAMERICANA, 2024)
In recent decades, water scarcity has increased considerably in Cuauhtémoc, Chihuahua – the most important apple-growing region of Mexico. Thus, the objective of this research is focused on evaluating growth and development responses in apple rootstocks graf ted with Golden Delicious subjected to four drought cycles, comparing them with the continuous irrigation treatment. Ten rootstocks were evaluated (B.9, M.9Nic29, G.41, G.202, G.890, G.210, G.30, M.7, MM.111 and MM.109) used in the commercial apple orchards in the area, where all the rootstocks were obtained during the 2020 growing season. The planting was carried out in 20-L pots in March 2020 and a substrate composed of compost, soil and sand was used in a ratio of 1:1:1. The recorded variables measured were moisture percentage in the soil, the leading branch growth, leaf water potential, total biomass, and ef ficient water use. The rootstocks B.9 and M.9 Nic29 showed good results in most of the variables studied. Rootstocks with good recovery of leaf water potential af ter recovery irrigation were found. These rootstocks were; B.9, M.9Nic29, MM.111 and G.210. The total biomass was statistically the same in G.30, G.41, MM.111, MM.109, G.202 and B.9. In conclusion, rootstocks tolerate a certain degree of drought and can contribute to improving water use, highlighting B.9.